Emerging trends in 2D nanotechnology that are redefining our understanding of "Nanocomposites". (August 2018) - Liu, Pingwei; Cottrill, Anton L.; Kozawa, Daichi; Koman, Volodymyr B.; Parviz, Dorsa; Liu, Albert Tianxiang; Yang, Jingfan; Tran, Thang Q.; Wong, Min Hao; Wang, Song; Strano, Michael S.
Graphical abstract: Highlights: Using semi-infinite 2D materials as nanofillers can achieve mechanical and functional reinforcements at the Platelet Limit. New techniques like folding, scrolling, and stacking can produce new forms of nanocomposites with well-dispersed 2D inclusions. The concept of a 3D macroscopic body comprised exclusively of 2D topology leads to nanocomposites with exotic functions. A key challenge is to scale up the production of large-area, high-quality 2D materials at a lower cost. Abstract: The goal of this review is to summarize the recent development of nanocomposites of 2D materials, especially polymer nanocomposites with large-area, high-quality 2D sheets, and more importantly, the future direction of this field. Scientists and engineers have a tendency to review and envision the future based on the past, but innovation does not work like this. Herein, we do not provide a comprehensive review of nanocomposites with 2D materials; rather, we highlight unusual or unconventional directions emerging for nanocomposite materials research. This forward-looking perspective of current trends focuses on new research directions. In this review, we summarize the fundamentals of nanocomposites in regards to the mechanical and functional reinforcement at the theoretical limit, and we briefly introduce the synthesis of large-area 2D materials with high quality and their controlled dispersion into matrix materials to achieve the maximum reinforcement predicted by theory. We continue with the classical and fundamentally important problem of the mechanical reinforcement in nanocomposites; that is, does the reinforcing contribution come from the modification of matrix or the direct mechanical reinforcement by the nanofillers? We present and discuss new forms of nanocomposites with layered and scrolled structure and well-positioned, semi-infinite 2D layers in detail. We also address the functional reinforcement from the continuous 2D sheets and the unusual applications of nanocomposites enabled by these functional 2D layers. In particular, we discuss fiber devices, such as an electromagnetic inductor and a thermal spiral conductor, an atomic-thick barrier film, a bioactive hybrid via attaching 2D layers to a living organism such as plant leaves, intelligent particle devices acting as state machines, and optical devices such as single photon emitters. With these, we further introduce the new nanocomposite concept of a three-dimensional (3D) macroscopic nanocomposite body comprised exclusively of 2D topology. Finally, we discuss the scalability challenges of the production process and the outlook of potential solutions. We hope this review and perspective can intrigue researchers who are currently working in the fields of 2D materials, polymers, and nanocomposites and provide some new insights to promote the future development of nanocomposites.